Anfibios del bosque nuboso de El Silencio de Los Ángeles, San Ramón de Alajuela, Costa Rica - Morera-Chacón, Brayan H. (2019)
We present the list of amphibians for the El Silencio de Los Ángeles Cloud Forest (Villa Blanca Hotel and Reserve) in San Ramón de Alajuela, Costa Rica, Central America. We performed nocturnal visual and acoustic surveys in the trail system, mainly from 2013 to 2014. We also received data from the local guides up to 2019. We compared the similarity of amphibian richness of our site against other premontane reserves in Costa Rica with a cluster analysis (Jaccard index, single linkage). We recorded 26 species distributed in 16 genera, eight families and two orders. Notrotiton gamezi was the only threatened species detected. The El Silencio de los Ángeles Cloud Forest site is around 80 % similar to San Lorencito River Station and 55% to Nectandra Reserve. Containing 12% of the Costa Rica’s amphibian richness, this premontane woodland should be considered among the most important clouded forest in Central Costa Rica for amphibian conservation.